Functional and Radiological Outcome of Revision Total Hip Arthroplasty in the Indonesian National Referral Hospital - Immanuel Panca Sitorus; Ismail Hadisoebroto Dilogo (The Hip and Knee Journal, 2022)
Background: Revision total hip arthroplasty (rTHA) rate has increased until 12-20% in the past few decades, despite the 95% success rate of THA approach in 10 years and 80% in 20 years. The most common causes of rTHA are dislocation, periprosthetic fracture, aseptic loosening, and periprosthetic joint infection. This study is aimed to describe the outcome of rTHA in Indonesia where there are limited types of revision implant and funding. Material and Methods: An analytic cross-sectional study was conducted on 31 rTHA in the Indonesian national referral hospital from January 2014 to December 2019. Data on the causes of rTHA was extracted. All subjects met the criteria underwent examination for functional outcome (Harris hip score) and radiological outcome (Harris or Engh criteria). All complications and outcomes after rTHA were identified. Results: Sixteen subjects met the criteria with the mean age of 48.13 (18.74). The most common causes of rTHA were dislocation, aseptic loosening, and perirosthetic joint infection (five cases each, 31.25%). The Harris hip score after complete rTHA was 79.42 (SD 6.14, range 70.50 – 91) with the mean follow up of 29.50 (SD 16.88, range 7 – 70 months). Only one possible loosening was identified in hybrid prosthesis (femoral component) from radiological exam. Three complications were observed, i.e. drop foot, recurrent dislocation, and extension knee contracture. Conclusion: Revision THA produces fair to good results in terms of functional outcome and no loosening in radiological exam. Revision THA is still a reliable technique to manage complications of THA.